Primary Management of Large Pancreatic Pseudoaneurysm by Ultrasound-Guided Percutaneous Thrombin Injection after Failure of Transarterial Pseudoaneurysm Embolization - Garg, Pawan Kumar; Khera, Pushpinder Singh; Rajagopal, Rengarajan; Mehta, Neeraj; Tarafdar, Swarnava (Journal of Clinical Interventional Radiology ISVIR, 2017)
Pancreatic pseudoaneurysm is a rare but life-threatening complication secondary to pancreatitis, surgery, trauma, or infection. Early treatment is advocated due to high risk of rupture and bleeding. Surgical treatment has traditionally been the first line but is associated with high morbidity. Transarterial embolization or exclusion is the treatment of choice; however, in cases with failure of endovascular treatment, percutaneous thrombin injection can be used successfully. We present a case of a large pancreatic pseudoaneurysm managed successfully with percutaneous ultrasound-guided thrombin injection after failure of transarterial management.
Keywords: pancreatic pseudoaneurysm; percutaneous thrombin injection; pseudoaneurysm embolization